Platinum-based catalyst with gold-doped surface as well as preparation method and application of platinum-based catalyst
Through ligand-mediated lattice strain and inducing transition metal discharge methods, gold doping on the surface of platinum-based catalysts is achieved, which solves the problem of surface transition metal dissolution of platinum-based catalysts in an acidic environment, significantly improves the activity and stability of the catalyst, and has the potential for industrial production.
Patent Information
- Application Number
- CN202510325859.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
Transition metal dissolution of the platinum-based catalyst on the surface of the surface of the fuel cell under the acidic working environment results in performance decay and damage to the proton exchange membrane, and existing improved methods such as carbon shell coating and tellurium doping have resource waste and performance limitations.
Through ligand-mediated lattice strain regulation and inducing transition metal discharge, gold doping on the surface of the platinum-based catalyst is achieved, Pt-Au bond length shrinkage and optimized the center position of the d-band, enhance the adsorption and regulation ability of oxygen-containing intermediates, and reduce the dissolution of platinum through the action of gold and platinum unsaturated coordination sites.
The activity and stability of the catalyst are significantly improved, the half-wave potential exceeds that of commercial Pt/C catalysts, the mass-specific activity reaches 0.87 A mgPt-1, and it is reduced by only 22.9% after the 10,000 cycle potential cycle, with high doped gold atom utilization rate and low cost industrial production potential.
Smart Images

Figure CN119852433A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation and application, and in particular to a platinum-based catalyst doped with surface gold, and a preparation method and application thereof. Background Art
[0002] As an efficient and environmentally friendly energy conversion device, fuel cells have attracted widespread attention due to their high energy conversion efficiency and pollution-free properties. In fuel cells, the oxygen reduction reaction (ORR) is the key cathode reaction, which has a slow reaction rate and requires efficient electrocatalysts to reduce the reaction energy barrier and accelerate the reaction.
[0003] Platinum-based catalysts are widely used in oxygen reduction reactions due to their excellent catalytic performance, but the scarcity and high cost of platinum resources limit their large-scale application. In order to reduce the amount of platinum used and improve the performance of the catalyst, researchers are committed to developing new platinum-based alloy catalysts. Platinum is considered to be a potential oxygen reduction electrocatalyst due to its unique electronic structure and good catalytic performance. However, the transition metal on the surface of platinum will dissolve in the acidic working environment of the fuel cell, resulting in the degradation of catalyst performance and damage to the proton exchange membrane.
[0004] In order to overcome this problem, researchers have tried to improve the properties of platinum-based intermetallic compounds by means of surface modification. For example, Chinese patent application CN202410799854.4 discloses a method for preparing a catalyst for a fuel cell assisted by nitrogen-containing organic small molecules. After the formation of the noble metal transition metal alloy, a nitrogen-containing organic liquid is mixed with the catalyst, and a carbon shell coating can be formed by simple sintering, thereby avoiding the migration of alloy particles and alleviating the precipitation of metal ions, which helps to overcome the problem of weak stability of platinum-based alloy catalysts at this stage. However, the external carbon shell is easily damaged during the use of the catalyst, and the carbon shell will affect the mass transfer of the reactants and thus reduce the catalytic performance.
[0005] Chinese patent application CN202410760180.7 discloses a tellurium-doped platinum-cobalt intermetallic compound catalyst. Tellurium doping not only effectively reduces the size of nanoparticles and increases their dispersion, but also effectively alleviates the dissolution of cobalt and inhibits the aggregation and growth of nanoparticles during stability testing. However, the tellurium doping exists not only on the surface of the nanoparticles but also inside, which leads to a large amount of tellurium used and a waste of resources. Summary of the invention
[0006] In view of the defects of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a platinum-based catalyst doped with surface gold, which uses the selective adsorption of ligands and transition metal surfaces to induce lattice compression strain. The strain effect causes the Pt-Au bond length to shrink when gold is subsequently doped, optimizes the center position of the d band, and enhances the adsorption and regulation ability of oxygen-containing intermediates; the method can also use trace amounts of gold to induce the transition metal on the surface of the nanoparticles to discharge, replace the transition metal with gold by inducing the transition metal discharge, and purify the surface while reducing the dissolution of platinum through the action of gold and platinum unsaturated coordination sites. The two work synergistically, while strain induces Au dispersion, the surface strain generated by the ligand can inhibit the surface migration of Au atoms and promote its atomic-level dispersion. At the same time, the strain sites (such as step edges) preferentially anchor Au atoms to form Pt-transition metal-Au tri-atom active sites.
[0007] The half-wave potential of the surface gold-doped platinum-based catalyst prepared by this method exceeds that of the commercial Pt / C catalyst by 49 mV and that of the non-gold-doped platinum-based catalyst by 30 mV. Its mass specific activity reaches 0.87 A mg Pt -1 , and has excellent stability, with the mass specific activity only decreasing by 22.9% after 10,000 cycles of potential cycling. To achieve the above object, the present invention provides a method for preparing a surface gold-doped platinum-based catalyst, comprising the following steps: S1, adding a platinum precursor, a transition metal precursor and carbon black into a dispersant and ultrasonically dispersing them, then rotary evaporating them to dryness, and then grinding them uniformly; S2, calcining the material obtained in step S1 under a reducing atmosphere at a temperature of 800-1000° C. for a time of 0.5-4 h, and then cooling the furnace to room temperature to obtain a platinum-based catalyst; S3, ultrasonically dispersing the material obtained in step S2 in ethanol, adding the ethanol solution of the ligand, stirring at room temperature, then rotary evaporating to dryness, and then grinding evenly; S4, ultrasonically dispersing the material obtained in step S3 in water, then adding a gold precursor salt and stirring at room temperature to induce transition metal discharge, filtering, washing and drying to obtain a platinum-based catalyst doped with gold on the surface.
[0008] Furthermore, in step S3, the ligand is mercaptopropionic acid or polyvinyl pyrrolidone, the concentration of the ligand is 0.01-0.1 mM, the volume is 5-10 ml, the stirring speed is 100-600 rpm, the stirring time is 12-24 h, and the rotary evaporation temperature is 80-90°C.
[0009] Furthermore, in step S4, the mass ratio of the material to the gold precursor salt is 1:(0.2-0.5).
[0010] Furthermore, in step S1, the molar ratio of platinum to transition metal is 1:(0.5~1.5).
[0011] Furthermore, when inducing transition metal discharge, the stirring speed is 100~600 rpm, and the stirring time is 1~6 h.
[0012] Furthermore, in step S1, the sum of the mass of platinum and transition metal in the platinum precursor and transition metal precursor is 40% to 80% of the mass of carbon black.
[0013] Furthermore, the gold precursor salt is one of chloroauric acid, gold chloride, gold(II) chloride, and potassium gold(II) cyanide; the carbon black is one of graphite black, ECP-600, ECP-300, and XC-72; the platinum precursor is one of chloroplatinic acid, potassium chloroplatinate, and potassium chloroplatinate, and the concentration of the platinum precursor is 0.01~0.2 M; the transition metal is cobalt, manganese, iron, copper, nickel, zinc, gallium, molybdenum, and tungsten, and the transition metal precursor is one of phthalocyanine salt, acetate, nitrate, and chloride; the concentration of the transition metal precursor is 0.05~0.2 M.
[0014] The present invention also provides a platinum-based catalyst doped with surface gold, which is prepared by the above-mentioned preparation method. The platinum-based catalyst doped with surface gold is carbon-supported metal nanoparticles, the platinum loading in the catalyst is 15-60wt%; and the particle size of the nanoparticles in the catalyst is 3-7 nm.
[0015] Furthermore, in the surface gold-doped platinum-based catalyst, the atomic fraction of gold is 0.1-5%.
[0016] The aforementioned surface gold-doped platinum-based catalyst can be used as a cathode catalyst for hydrogen fuel cells.
[0017] The beneficial effects of the present invention are: 1. The preparation method of the platinum-based catalyst doped with surface gold provided by the present invention is firstly to prepare the platinum-based nanoparticle catalyst by the impregnation calcination reduction method, then to regulate the lattice strain mediated by the ligand, to impregnate the ligand solution, and finally to induce the transition metal discharge on the surface of the nanoparticle by the method of inducing transition metal discharge to achieve the surface doping of gold. The surface doping of gold can not only reduce the dissolution of platinum by being adjacent to the unsaturated coordination site of platinum, but also remove the transition metal on the surface to purify the surface of the nanoparticle. The two act synergistically. While the strain induces the dispersion of Au, the surface strain generated by the ligand can inhibit the surface migration of Au atoms and promote its atomic-level dispersion. At the same time, the strain site (such as the step edge) preferentially anchors the Au atom to form a Pt-transition metal-Au tri-atom active site, thereby maintaining the activity and stability of the catalyst.
[0018] 2. In the prior art, platinum-based nanoparticles are often prone to platinum dissolution during the oxygen reduction reaction, resulting in a reduction in catalyst active sites and a decrease in performance. The present invention dopes gold on the surface of platinum-based nanoparticles, so that gold atoms can contact the under-coordinated sites of platinum to form stable chemical bonds. This structure can effectively inhibit the formation of oxide species on the surface of platinum, thereby reducing the dissolution of platinum. In addition, in the process of induced transition metal discharge, gold salts can induce the discharge of transition metals and replace the transition metals on the surface of nanoparticles with gold. This process can not only purify the catalyst surface and reduce surface impurities. Gold doping can also optimize the electronic structure of platinum-based catalysts. The introduction of gold atoms can adjust the electronic state of platinum-based alloys, making them more conducive to the adsorption and activation of oxygen molecules, thereby reducing the activation energy of oxygen reduction reactions. This optimization of electronic structure not only improves the activity of the catalyst, but also enables it to efficiently promote oxygen reduction reactions under lower kinetic conditions. The activity of the catalyst is significantly increased, thereby improving the overall performance of the catalyst.
[0019] 3. The half-wave potential of the surface gold-doped platinum-based catalyst prepared by this method exceeds that of the commercial Pt / C catalyst by 49 mV and that of the non-gold-doped platinum-based catalyst by 30 mV. Its mass specific activity reaches 0.87 A mg Pt -1 , and has excellent stability, with the mass specific activity only decreasing by 22.9% after 10,000 cycles of potential cycling.
[0020] 4. This method has a high utilization rate of doped gold atoms, a simple preparation process, low cost, good reproducibility, and low equipment requirements, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a comparison chart of the X-ray diffraction (XRD) standard card of the catalyst prepared in Example 1 and commercial Pt / C.
[0022] Figure 2 The scanning electron microscope (SEM) image of the catalyst prepared in Example 1 and the EDS mapping element distribution map of the corresponding area.
[0023] Figure 3 This is a transmission electron microscope (TEM) image of the catalyst prepared in Example 1.
[0024] Figure 4 This is a comparison diagram of the rotating disk electrode polarization curves in acid medium of the catalyst prepared in Example 1 and the control group and the commercial Pt / C catalyst.
[0025] Figure 5Comparison of polarization curves and cyclic voltammetry curves of the catalyst prepared in Example 1 before and after 10,000 potential cycles at 0.6 V to 0.95 V (vs. RHE), as well as comparison of mass specific activity and electrochemical specific surface area calculated at a fixed polarization potential of 0.9 V.
[0026] Figure 6 This is the thermogravimetric (TG) curve of the catalyst prepared in Example 1 under air conditions.
[0027] Figure 7 It is a comparison diagram of the polarization curves of the catalysts obtained in Examples 1-3 and Comparative Examples 1-2.
[0028] Figure 8 It is a comparison diagram of the cyclic voltammetry curves of the catalysts obtained in Examples 1-3 and Comparative Examples 1-2.
[0029] Fig. 9 This is a transmission electron microscope (TEM) image of the catalyst obtained in Comparative Example 2.
[0030] Fig.10 It is a comparison diagram of the polarization curves of the catalysts prepared in Comparative Example 3 and Example 1. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0032] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0033] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0034] In the prior art, platinum-based nanoparticles are often prone to platinum dissolution during the oxygen reduction reaction, resulting in a reduction in catalyst active sites and a degradation of performance.
[0035] The present invention provides a method for preparing a platinum-based catalyst doped with surface gold, wherein the platinum-based nanoparticle catalyst is first prepared by an impregnation calcination reduction method, and then a transition metal discharge is induced on the surface of the nanoparticles by an induction transition metal discharge method to achieve surface gold doping. The surface gold doping can not only reduce the dissolution of platinum by being adjacent to the unsaturated coordination sites of platinum, but also remove the transition metal on the surface to purify the surface of the nanoparticles, thereby maintaining the activity and stability of the catalyst.
[0036] In one aspect, the present invention provides a method for preparing a surface gold-doped platinum-based catalyst, comprising the following steps: S1, adding platinum precursor, transition metal precursor and carbon black into a dispersant for ultrasonic dispersion, then rotary evaporation to dryness, and then grinding to uniformity; wherein the molar ratio of platinum to transition metal is Pt:Co=1:(0.5~1.5); The carbon black is one of graphite carbon black (GCB), ECP-600, ECP-300, and XC-72; The platinum precursor is one of chloroplatinic acid, potassium chloroplatinate, and potassium chloroplatinite, and the concentration of the platinum precursor is 0.01-0.2M; The transition metal precursor is one of phthalocyanine salt, acetate, nitrate, and chloride; the concentration of the transition metal precursor is 0.05-0.2 M. The transition metal is cobalt, manganese, iron, copper, nickel, zinc, gallium, molybdenum, and tungsten.
[0037] Among them, the sum of the mass of platinum and transition metal in the platinum precursor and transition metal precursor is 40%~80% of the mass of carbon black.
[0038] The dispersant is deionized water, anhydrous ethanol or acetone; During ultrasonic dispersion, the ultrasonic time is more than 60 min; preferably, the ultrasonic dispersion is 60 - 90 min; The rotary evaporation temperature is 60~100℃.
[0039] S2, calcining the material obtained in step S1 under a reducing atmosphere at a temperature of 800-1000° C. for a time of 0.5-4 h, and then cooling the furnace to room temperature to obtain a platinum-based catalyst; The reducing atmosphere is one of hydrogen, hydrogen-argon mixed gas, and hydrogen-nitrogen mixed gas.
[0040] Preferably, the calcination temperature is 800-900° C., and the calcination time is 0.5-1.5 h.
[0041] S3, ultrasonically dispersing the material obtained in step S2 in ethanol, adding the ethanol solution of the ligand, stirring at room temperature, then rotary evaporating to dryness, and then grinding evenly; The ligand is one of mercaptopropionic acid (MPA) or polyvinylpyrrolidone (PVP), with a concentration of 0.01-0.1 mM and a volume of 5-10 ml.
[0042] The stirring speed is 100~600 rpm, the stirring time is 12~24 h, the rotary evaporation temperature is (80~90)℃, and the rotary evaporation temperature is 60~90℃.
[0043] S4, ultrasonically dispersing the material obtained in step S3 in water, then adding a gold precursor salt and stirring at room temperature to induce transition metal discharge, filtering and cleaning, and drying in a vacuum oven to obtain a platinum-based catalyst doped with surface gold. The mass ratio of the material to the gold precursor salt is 1: (0.2-0.5).
[0044] The gold precursor salt is one of chloroauric acid, gold chloride, gold(II) chloride and potassium gold(II) cyanide.
[0045] When inducing transition metal discharge, the stirring speed is 100~600 rpm and the stirring time is 1~6 h.
[0046] The ultrasonic dispersion time is 10~30 min; the drying temperature is 60~90℃.
[0047] In the embodiments of the present application, the selective adsorption of ligands and transition metal surfaces is used to induce lattice compression strain. The strain effect causes the Pt-Au bond length to shrink during subsequent gold doping, optimizes the center position of the d band, and enhances the adsorption and regulation ability of oxygen-containing intermediates; trace gold is used to induce the transition metal on the surface of the nanoparticles to discharge, and the transition metal is replaced with gold by inducing the transition metal discharge. While purifying the surface, the gold and platinum unsaturated coordination sites act to reduce the dissolution of platinum. The surface doping of gold can not only reduce the dissolution of platinum by being adjacent to the unsaturated coordination sites of platinum, but also induce the discharge of transition metals to remove the transition metals on the surface of the catalyst to enhance the catalytic activity. The two work synergistically, while the strain induces the dispersion of Au, the surface strain generated by the ligand can inhibit the surface migration of Au atoms and promote their atomic-level dispersion. At the same time, the strain sites (such as step edges) preferentially anchor Au atoms to form Pt-Co-Au three-atom active sites.
[0048] In a second aspect, the present invention also provides a platinum-based catalyst doped with gold on the surface, which is prepared by the above-mentioned preparation method. The platinum-based catalyst doped with gold on the surface is carbon-supported metal nanoparticles, the platinum loading in the catalyst is 15-60wt%; and the particle size of the nanoparticles in the catalyst is 3-7 nm.
[0049] In the surface gold-doped platinum-based catalyst, the atomic fraction of gold is 0.1~5%.
[0050] The signal of gold element was observed in EDS mapping, indicating the successful doping of gold.
[0051] The aforementioned surface gold-doped platinum-based catalyst can be used as a cathode catalyst for hydrogen fuel cells.
[0052] The preparation method of the surface gold-doped platinum-based catalyst provided by the present invention is described below in conjunction with specific examples. Unless otherwise specified, the raw materials and reagents in the examples of the present application are purchased through commercial channels.
[0053] Example 1 This embodiment provides a method for preparing a platinum-based catalyst with a gold-doped surface, firstly preparing a platinum-based catalyst by an impregnation calcination method, and then forming a gold-doped surface by an induced transition metal discharge method, specifically comprising the following steps: (1) 25.8 mg of carbon black (acid-graphitized carbon black) was added to 40 ml of ethanol, and then 8.10 mL (0.01 M) chloroplatinic acid ethanol solution and 0.81 mL CoCl2 (0.1 M) ethanol solution were added to the mixture and ultrasonicated for 60 min. Next, the obtained uniform mixed solution was heated to 90 °C in a rotary evaporator and dried, and the obtained powder was collected and ground uniformly.
[0054] (2) The powder obtained in step (1) is placed in a tubular furnace, heated to 800°C at a heating rate of 10°C / min in a hydrogen-argon mixed atmosphere and kept at this temperature for 1 h, and then cooled to room temperature in the furnace to obtain a platinum-based catalyst.
[0055] (3) Add 23 mg of the powder obtained in step (2) to 40 ml of ethanol and ultrasonicate for 60 min. Then add 7.7 ml of ethanol solution (0.05 mM) of mercaptopropionic acid (MPA) and stir at room temperature for 15 h. Then, heat the obtained uniform mixed solution to 60 °C in a rotary evaporator and dry it. Collect the obtained powder and grind it evenly.
[0056] (4) 20 mg of the powder obtained in step (3) was added to deionized water, and ultrasonicated for 30 min to form a uniform dispersion. Then 8 mg of chloroauric acid was added, and the mixture was stirred at 400 rpm for 6 h. The mixture was then filtered and washed with deionized water, and dried in an oven at 70°C to obtain a platinum-based catalyst doped with gold on the surface.
[0057] Control group The control group prepared a platinum-cobalt catalyst; the main difference between the control group and Example 1 is that step (3) and step (4) were not performed, and the other steps were substantially the same as those in Example 1 and will not be described again.
[0058] Figure 1The X-ray diffraction (XRD) standard card comparison chart of the surface gold-doped platinum-based catalyst prepared in Example 1 and the commercial Pt / C. It can be seen that the catalyst prepared in Example 1 has the PtCo-specific (001) and (110) superlattice characteristic peaks at around 23° and 33°, indicating that a long-range ordered atomic arrangement structure has been formed.
[0059] Figure 2 The scanning electron microscope (SEM) image of the catalyst prepared in Example 1 and the EDS mapping element distribution map of the corresponding area. The carbon support structure of the catalyst can be seen, and no agglomerated metal particles are found, indicating that the particles are evenly loaded on the carbon support and have a small particle size. The results of EDS mapping show that the sample contains three elements, platinum, cobalt and gold, and the elements are evenly distributed, indicating that gold is successfully doped into the surface of the nanoparticles by inducing transition metal discharge.
[0060] Figure 3 This is a transmission electron microscope (TEM) image of the catalyst obtained in Example 1. It can be observed that the dark nanoparticles are evenly distributed on the carbon support without agglomeration. The particle size of the nanoparticles in the catalyst is 3-7 nm.
[0061] Figure 4 The polarization curves of the catalysts obtained in Example 1 and the control group are compared with the rotating disk polarization curves of the commercial Pt / C catalyst in the acid medium. The electrolyte solution is 0.1 M HClO4 saturated with O2; the scanning rate is 10 mV / s; the scanning voltage range is -0.25 ~ 0.8 V; the rotation speed is rpm=1600.
[0062] From the polarization curve after iR compensation, it can be seen that the half-wave potential of the prepared surface gold-doped platinum-based catalyst exceeds that of the commercial Pt / C catalyst by 49 mV and that of the non-gold-doped platinum-cobalt catalyst by 30 mV.
[0063] Figure 5 It is a comparison of the polarization curves of the catalyst obtained in Example 1 before and after 10,000 potential cycles at a scan rate of 100 mA / s at 0.6 V~0.95 V (vs. RHE), and a comparison of the mass specific activity calculated at a fixed polarization potential of 0.9 V.
[0064] It can be seen that after 10,000 cycles of potential cycling, the polarization curve and cyclic voltammetry curve of the homemade catalyst changed little compared to Pt / C. At the beginning, the mass specific activity reached 0.87 A mg Pt -1 , which is 6.7 times that of commercial Pt / C (0.13 A mg Pt -1), and after 10,000 cycles of potential cycling, the mass specific activity only decreased by 22.9%, which is significantly better than commercial Pt / C, reflecting its excellent stability.
[0065] Figure 6 This is the thermogravimetric (TG) curve of the catalyst obtained in Example 1 under air conditions. Starting from 300°C, a large amount of mass loss occurred due to carbon oxidation, and the final catalyst loading was 40wt%.
[0066] Example 2-3 and Comparative Example 1-2 Example 2-3 and Comparative Example 1-2 provide a method for preparing a surface gold-doped platinum-based catalyst. Compared with Example 1, the difference is that the mass ratio of the material to the gold precursor salt in step S3 is changed, as shown in the following table; the rest is roughly the same as Example 1 and will not be repeated here.
[0067] Figure 7 The polarization curve comparison diagram of the catalysts obtained in Example 1-3 and Comparative Example 1-2, wherein the electrolyte solution is 0.1 M HClO4 saturated with O2; the scanning rate is 10 mV / s; the scanning voltage range is -0.25 to 0.8 V; and the rotation speed is rpm=1600.
[0068] Figure 8 The cyclic voltammetry curves of the catalysts obtained in Examples 1-3 and Comparative Examples 1-2 are compared, wherein the electrolyte solution is 0.1 M HClO4 saturated with N2; the scanning rate is 50 mV / s; and the scanning voltage range is 0.05 to 1.1 V.
[0069] As can be seen from the chart, when the mass ratio of the material to the gold precursor salt is less than 1:0.2, due to too little gold doping on the surface, the half-wave potential and active area of the obtained catalyst sample are similar to those of the catalyst sample without gold doping. When the mass ratio of the material to the gold precursor salt is greater than 1:0.5, due to the intensified particle agglomeration, the half-wave potential and active area of the obtained catalyst sample decrease compared with Example 1-3.
[0070] Fig. 9 This is a transmission electron microscope (TEM) image of the catalyst obtained in Comparative Example 2. It can be observed that a large number of dark-colored nanoparticles are aggregated on the carbon support.
[0071] Comparative Example 3 Comparative Example 3 provides a method for preparing a platinum-based catalyst doped with surface gold. Compared with Example 1, the difference is that step (3) is not performed, and the other steps are substantially the same as those in Example 1 and are not described again.
[0072] Fig.10The polarization curves of the catalysts obtained in Example 1 and Comparative Example 3 are compared. The electrolyte solution is 0.1 M HClO4 saturated with O2; the scanning rate is 10 mV / s; the scanning voltage range is -0.25 to 0.8 V; and the rotation speed is rpm=1600.
[0073] As can be seen from the figure, the half-wave potential of Example 1 exceeds that of the catalyst prepared in Comparative Example 3 by 29 mV. This is because the lattice compression strain changes the atomic spacing of platinum, thereby regulating the center position of the d-band of platinum. The ligand-mediated lattice strain regulation is not carried out, resulting in no strain being introduced, and the d-band center may be too high or too low, resulting in an imbalance in the adsorption intensity of oxygen-containing intermediates (such as O*, OH*, OOH*); the rate-determining step of the oxygen reduction reaction (ORR) (such as O2 dissociation or OH⁻ desorption) decreases in efficiency due to the mismatch of the adsorption energy barrier, resulting in a significant decrease in catalytic activity.
[0074] The synergistic effect is lost, Au cannot inhibit platinum oxidation and enhance corrosion resistance, which accelerates the deactivation of the catalyst and leads to the deterioration of its overall performance.
[0075] Embodiment 4-6 Example 4-6 provides a method for preparing a surface gold-doped platinum-based catalyst. Compared with Example 1, the difference is that the type of gold precursor salt in step S3 is changed, as shown in the following table; the rest is roughly the same as Example 1 and will not be repeated here.
[0076] Experiments show that Examples 4-6 can successfully produce surface gold-doped platinum-based catalysts.
[0077] Example 7 Example 7 provides a method for preparing a surface gold-doped platinum-based catalyst. Compared with Example 1, the difference is that 7.7 ml of mercaptopropionic acid in step (3) is replaced by 5.1 ml of polyvinyl pyrrolidone; the rest is roughly the same as Example 1 and will not be repeated here.
[0078] Embodiment 8-15 Embodiment 8-15 provides a method for preparing a surface gold-doped platinum-based catalyst. Compared with Embodiment 1, the difference is that the type of transition metal salt in step (1) is changed, as shown in the following table; the rest is roughly the same as Embodiment 1 and will not be repeated here.
[0079] Experiments show that Examples 8-15 can successfully produce surface gold-doped platinum-based catalysts.
[0080] It should be noted that the carbon black may be one of ECP-600, ECP-300, and XC-72. The platinum precursor may be one of potassium chloroplatinate and potassium chloroplatinate. The transition metal precursor may be one of phthalocyanine transition metal, acetic acid transition metal, and nitrate transition metal.
[0081] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a surface gold-doped platinum-based catalyst, characterized in that: The steps include: S1, adding a platinum precursor, a transition metal precursor and carbon black into a dispersant and ultrasonically dispersing them, then rotary evaporating them to dryness, and then grinding them uniformly; S2, calcining the material obtained in step S1 under a reducing atmosphere at a temperature of 800-1000° C. for a time of 0.5-4 h, and then cooling the furnace to room temperature to obtain a platinum-based catalyst; S3, ultrasonically dispersing the material obtained in step S2 in ethanol, adding the ethanol solution of the ligand, stirring at room temperature, then rotary evaporating to dryness, and then grinding evenly; S4, ultrasonically dispersing the material obtained in step S3 in water, then adding a gold precursor salt and stirring at room temperature to induce transition metal discharge, filtering, washing and drying to obtain a platinum-based catalyst doped with gold on the surface.
2. The method for preparing a surface gold-doped platinum-based catalyst according to claim 1, characterized in that: In step S3, the ligand is mercaptopropionic acid or polyvinyl pyrrolidone, the concentration of the ligand is 0.01-0.1 mM, the volume is 5-10 ml, the stirring speed is 100-600 rpm, the stirring time is 12-24 h, and the rotary evaporation temperature is 80-90°C.
3. The method for preparing a surface gold-doped platinum-based catalyst according to claim 1, characterized in that: In step S4, the mass ratio of the material to the gold precursor salt is 1:(0.2-0.5).
4. The method for preparing a surface gold-doped platinum-based catalyst according to claim 1, characterized in that: In step S1, the molar ratio of platinum to transition metal is 1:(0.5-1.5).
5. The method for preparing a surface gold-doped platinum-based catalyst according to claim 1, characterized in that: When inducing transition metal discharge, the stirring speed is 100~600 rpm and the stirring time is 1~6 h.
6. The method for preparing a surface gold-doped platinum-based catalyst according to claim 1, characterized in that: In step S1, the mass sum of platinum and transition metal in the platinum precursor and transition metal precursor is 40% to 80% of the mass of carbon black.
7. The method for preparing a surface gold-doped platinum-based catalyst according to claim 1, characterized in that: The gold precursor salt is one of chloroauric acid, gold chloride, gold(II) chloride, and potassium gold(II) cyanide; the carbon black is one of graphite black, ECP-600, ECP-300, and XC-72; the platinum precursor is one of chloroplatinic acid, potassium chloroplatinate, and potassium chloroplatinate, and the concentration of the platinum precursor is 0.01-0.2 M; the transition metal is cobalt, manganese, iron, copper, nickel, zinc, gallium, molybdenum, and tungsten, and the transition metal precursor is one of phthalocyanine salt, acetate, nitrate, and chloride; the concentration of the transition metal precursor is 0.05-0.2 M.
8. A platinum-based catalyst doped with gold on the surface, prepared by the method for preparing a platinum-based catalyst doped with gold on the surface according to any one of claims 1 to 7, characterized in that: The platinum-based catalyst doped with gold on the surface is carbon-supported metal nanoparticles, the loading amount of platinum in the catalyst is 15-60wt%; and the particle size of the nanoparticles in the catalyst is 3-7 nm.
9. The surface gold-doped platinum-based catalyst according to claim 8, characterized in that: In the surface gold-doped platinum-based catalyst, the atomic fraction of gold is 0.1-5%.
10. An application of a platinum-based catalyst doped with gold on the surface, characterized in that: The surface gold-doped platinum-based catalyst is prepared according to the preparation method described in any one of claims 1-7 or is the surface gold-doped platinum-based catalyst described in any one of claims 8-9; the surface gold-doped platinum-based catalyst is used as a cathode catalyst for a hydrogen fuel cell.
Citation Information
Patent Citations
Preparation method and application of tellurium-doped platinum-cobalt intermetallic compound catalyst
CN118659004A
Catalyst for fuel cell as well as preparation method and application of catalyst
CN118738424A
Au@Au / Pt core-shell structure nano catalyst applied to alcohol fuel cells
CN108110265A
Carbon-supported platinum-based core-shell catalyst and preparation method thereof
CN116979074A
Carbon-supported Pt-based alloy nano-catalyst as well as preparation method and application thereof
CN117117224A
Cited By
Rapid conversion method of platinum oxidation state-highly metallic state of hafnium-doped platinum catalyst
CN122025680A
Process for the rapid conversion of the oxidation state of platinum in hafnium-doped platinum catalysts to the high metal state
CN122025680B